2018
DOI: 10.1097/bsd.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cervical Spine Motion in Different Types of Cervical Alignment

Abstract: Level 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…As a result, the upper cervical spine was not required to compensate for postoperative subaxial malalignment after ACDF. Sessumpun et al 35 found increased upper cervical spine motion for those with global cervical kyphosis with the mean CL of −8.2 degrees in their patient cohort (compared with 15.9 degrees in the present study). Future research in a cohort with significant cervical spine kyphosis or cSVA > 40 mm may better elucidate these relationships.…”
Section: Discussioncontrasting
confidence: 42%
“…As a result, the upper cervical spine was not required to compensate for postoperative subaxial malalignment after ACDF. Sessumpun et al 35 found increased upper cervical spine motion for those with global cervical kyphosis with the mean CL of −8.2 degrees in their patient cohort (compared with 15.9 degrees in the present study). Future research in a cohort with significant cervical spine kyphosis or cSVA > 40 mm may better elucidate these relationships.…”
Section: Discussioncontrasting
confidence: 42%
“…For the overall ROM of the cervical spine (C1-C7), our results showed that the ROM of the kyphosis group increased by approximately 41.2% compared with the normal group during left-right lateral bending movements. Similarly, Sessumpun et al [27] used MRI technology to study the 2D motion of cervical vertebrae with different curvatures and found that the overall ROM in a cervical kyphosis group increased by 38.8% compared with a normal curvature group. Although their results were similar to the present study, data on changes in mobility during left-right rotation and exion-extension movements were not reported separately in the Sessumpun et al study.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the sample of both groups were little since only patients with CSM performed 3-level ACDF were enrolled. Then, global cervical alignment was expressed by CL, which could not ideally describe total shapes of cervical spine such as sigmoid-S-type since it might effect the spinal canal volume [ 29 ] and result in a shape-derived symptom. Finally, the conclusion was suitable for 3-level ACDF on CSM but might not for other types such as cervical spondylotic radiculopathy, where the nerve root could be effected by the height of intervertebral foramen result from the change of cervical alignment.…”
Section: Discussionmentioning
confidence: 99%